INFLUENCE OF MIX PROPORTION ON WORKABILITY OF LATERIZED CONCRETE - Muhammad, Amina; Abejide, O. S.; Kaura, J. M. (FUDMA JOURNAL OF SCIENCES, 2023)
The increase in infrastructural development in the tropic has led to high demand for concrete production. Consequently, its constituents became very scarce and costly, especially the naturally occurring constituents. Laterite as an abundant naturally occurring material in the tropics is only put in use as filling material or in road construction. This study presents the determination of influence of nominal mix proportion (1:2:4, 1:1.5:3 and 1:1:2) at a constant water cement ratio of 0.5 with laterite fully replacing sand (fine aggregate). 72 numbers of cubes of size  100 mm were prepared for the different concretes, while 12 numbers were cast for each mix proportion and cured in the curing tank at 3, 7, 14, 28 days. Though the laterite was found to be a normal weight aggregate, it was also identified as A – 7 – 6, medium plastic clayey and porous material, with a specific gravity of 2.59.  For the fresh concrete, the slump value and degree of workability were obtained using the Vee-bee consistometer and slump tests in both laterite and conventional concrete in all the three mix proportions (1:2:4 : 0.5, 1 : 1.5 : 3 : 0.5, 1 : 1 : 2 : 0.5). The Vee bee second for the mix proportions (1:2:4 , 1:1.5:3 and 1:1:2 ) are 13:18 , 09:44 and 6.0 for the conventional concrete while 14:47 , 12: 41 and 9:30 for Laterized concrete.